Carbohydrate does not augment exercise-induced protein accretion versus protein alone - Staples, A. W.; Burd, N. A.; West, D. W. D.; Currie, K. D.; Atherton, P. J.; Moore, D. R.; Rennie, M. J.; MacDonald, M. J.; Baker, S. K.; Phillips, S. M. (Medicine & Science in Sports & Exercise, 2011)
Purpose: We tested the thesis that CHO and protein coingestion would augment muscle protein synthesis (MPS) and inhibit muscle protein breakdown (MPB) at rest and after resistance exercise. Methods: Nine men (age = 23.0 ± 1.9 yr, body mass index = 24.2 ± 2.1 kg·m-2) performed two unilateral knee extension trials (four sets × 8-12 repetitions to failure) followed by consumption of 25 g of whey protein (PRO) or 25 g of whey protein plus 50 g of maltodextrin (PRO + CARB). Muscle biopsies and stable isotope methodology were used to measure MPS and MPB. Results: The areas under the glucose and insulin curves were 17.5-fold (P < 0.05) and 5-fold (P < 0.05) greater, respectively, for PRO + CARB than for PRO. Exercise increased MPS and MPB (both P < 0.05), but there were no differences between PRO and PRO + CARB in the rested or exercised legs. Phosphorylation of Akt was greater in the PRO + CARB than in the PRO trial (P < 0.05); phosphorylations of Akt (P = 0.05) and acetyl coA carboxylase-ß (P < 0.05) were greater after exercise than at rest. The concurrent ingestion of 50 g of CHO with 25 g of protein did not stimulate mixed MPS or inhibit MPB more than 25 g of protein alone either at rest or after resistance exercise. Conclusions: Our data suggest that insulin is not additive or synergistic to rates of MPS or MPB when CHO is coingested with a dose of protein that maximally stimulates rates of MPS.